"To hope was to expect": The impact of perspective taking and forecast type on wishful thinking. (10th January 2020) - Rose, Jason P.; Aspiras, Olivia
Abstract: When forecasting future outcomes, people tend to believe that the outcomes they want to happen are also likely to happen. Despite numerous attempts, few systematic factors have been identified that consistently and robustly reduce wishful thinking (WT) effects. Using elections and sporting event outcomes as contexts, three experiments examined whether taking the perspective of a political rival or opposing fan reduced WT effects. We also examined whether making deliberative (vs. intuitive‐based) forecasts was associated with lower WT effects. Online adult samples of U.S. citizens from Mechanical Turk and U.S. college students provided their preferences and forecasts for the U.S. presidential election (Experiments 1 and 2) and a sports competition outcome (Experiment 3). Critically, some participants received perspective taking prompts immediately before providing forecasts. First, results revealed reductions in WT effects when participants engaged in perspective taking. Interestingly, this effect only emerged when intuitive‐based forecasts were made first (Experiment 3). Second, intuitive‐based forecasts revealed stronger evidence of WT effects. Finally, we found that perspective taking and forming forecasts deliberately promoted a shift in focus away from preferences and toward a consideration of the relative strengths and weaknesses of the entities (i.e., candidates and teams). Theoretical implications for understanding WT effects and applied implications for developing interventions are discussed.